The future of hospitality is storytelling: conceptualising the visitor’s journey - Carissa Baker (Research in Hospitality Management)
Storytelling has become an increasingly important aspect of hospitality and tourism that can have several positive impacts on visitors. This article argues for an understanding of narrative structure in the guest experience as well as a reconceptualisation of the visitor’s journey as being one of a character traversing a storyworld. It also suggests that narrative implementation should become deeper and more experimental, with structures and organisational types in place in attractions. The article presents 20 cases of narrative in global hospitality and tourism contexts that illustrate these principles.